2004
DOI: 10.1161/01.cir.0000121361.01862.a4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Anomalies in Alagille Syndrome

Abstract: Background-Alagille syndrome (AGS) is a dominantly inherited multisystem disorder involving the liver, heart, eyes, face, and skeleton, caused by mutations in Jagged1. Intracranial bleeding is a recognized complication and cause of mortality in AGS. There are multiple case reports of intracranial vessel abnormalities and other vascular anomalies in AGS. The objective of this study was to characterize the nature and spectrum of vascular anomalies in AGS. Methods and Results-Retrospective chart review of 268 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(88 citation statements)
references
References 25 publications
(9 reference statements)
0
85
1
Order By: Relevance
“…Consistent with this finding, we have previously shown that inhibition of Notch in neural crest cells, which act as smooth muscle precursors in the pulmonary artery, results in pulmonary artery stenosis and other congenital heart defects reminiscent of those seen in Alagille syndrome (22). Defects in smooth muscle development may also be responsible for other vascular pathologies seen in patients with Alagille syndrome, such as a predisposition to intracranial bleeding (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this finding, we have previously shown that inhibition of Notch in neural crest cells, which act as smooth muscle precursors in the pulmonary artery, results in pulmonary artery stenosis and other congenital heart defects reminiscent of those seen in Alagille syndrome (22). Defects in smooth muscle development may also be responsible for other vascular pathologies seen in patients with Alagille syndrome, such as a predisposition to intracranial bleeding (28).…”
Section: Resultsmentioning
confidence: 99%
“…One of the principal findings in Alagille syndrome is congenital heart disease, especially pulmonary artery stenosis, and vascular disease including a predisposition to intracranial bleeding (27,28). Therefore, a better understanding of the role of Jag1 in cardiovascular development promises to provide insight into the pathogenesis of Alagille syndrome and other forms of congenital heart and vascular diseases.…”
mentioning
confidence: 99%
“…In mice, mutation of Jagged1 results in lethality at embryonic day 10.5 and is accompanied by abnormal vascular patterning and failure to remodel the primary vascular plexus in the yolk sac (33). In humans, Alagille syndrome, caused by a mutation in the Notch ligand Jagged1 gene, is associated with arteriopathy, most notably involving the pulmonary artery (34). Similarly, the human CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) syndrome is a heritable arteriopathy caused by a mutation in the human Notch3 gene (35).…”
Section: Vascular Smooth Muscle Cells (Vsmcs)mentioning
confidence: 99%
“…In Alagille syndrome, however, death in the pediatric age range, secondary to intracranial bleeding after mild or no trauma, is common [37,41,42], since they tend also to have more vasculopathies than the normal population [41]. These range from stenosis of the internal carotid artery, intracerebral aneurysms, and non-atherosclerotic carotid artery anomalies to thin-walled vessels and moyamoya-like changes [42].…”
Section: Discussionmentioning
confidence: 99%